Environmental levels and human body burdens of per- and polyfluoroalkyl substances in Africa: A critical review - Ssebugere, Patrick; Sillanpää, Mika; Matovu, Henry; Wang, Zhanyun; Schramm, Karl-Werner; Omwoma, Solomon; Wanasolo, William; Chelangat Ngeno, Emily; Odongo, Silver (Science of the Total Environment, 2020)
Per- and polyfluoroalkyl substances (PFASs) are known organic pollutants with adverse health effects on humans and the ecosystem. This paper synthesises literature about the status of the pollutants and their precursors, identifies knowledge gaps and discusses future perspectives on the study of PFASs in Africa. Limited data on PFASs prevalence in Africa is available because there is limited capacity to monitor PFASs in African laboratories. The levels of PFASs in Africa are higher in samples from urban and industrialized areas compared to rural areas. Perfluorooctane sulfonic acid (PFOS) and perfluorooctanoic acid (PFOA) are the dominant PFASs in human samples from Africa. Levels of PFOS and PFOA in these samples are lower than or comparable to those from industrialised countries. PFOA and PFOS levels in drinking water in Africa are, in some cases, higher than the EPA drinking water guidelines suggesting potential risk to humans. The levels of PFASs in birds’ eggs from South Africa are higher, while those in other environmental media from Africa are lower or comparable to those from industrialised countries. Diet influences the pollutant levels in fish, while size and sex affect their accumulation in crocodiles. No bioaccumulation of PFASs in aquatic systems in Africa could be confirmed due to small sample sizes. Reported sources of PFASs in Africa include municipal landfills, inefficient wastewater treatment plants, consumer products containing PFASs, industrial wastewater and urban runoff. Relevant stakeholders need to take serious action to identify and deal with the salient sources of PFASs on the African continent.
Keywords: Per- and polyfluoroalkyl substances; PFOA; PFOS; Human body burdens; Africa